Performance Improvement Strategy via Talent Management and Employee Retention in Jakarta MSMEs - Supana Supana; Aminullah Aminullah; Suyanto Suyanto; Sukesi Sukesi; Nur Sayidah; Slamet Riyadi; Siti Marwiyah; Yuliansyah Yuliansyah (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of Business Reputation, Leadership, and Organizational Justice on Talent Management Strategies, Employee Retention, and MSME Performance Strategies, while examining the mediating roles of Talent Management Strategies and Employee Retention.. Research Methodology: A quantitative approach was employed using data from 189 MSMEs selected through purposive sampling. The data were analyzed using SPSS and Smart PLS 3 to test both direct and indirect relationships among variables. Results: Findings indicate that Business Reputation significantly affects Talent Management Strategies (p = 0.000), Employee Retention (p = 0.026), and MSME Performance (p = 0.000). Leadership shows no significant effect on any dependent variable, while Organizational Justice significantly influences Talent Management Strategies (p = 0.008) but not Employee Retention or MSME Performance. Indirectly, Talent Management Strategies mediate the effects of Business Reputation and Organizational Justice on Employee Retention, whereas Employee Retention does not mediate the effect of the main variables on performance. However, a combined mediation of Talent Management Strategies and Employee Retention significantly links Business Reputation to MSME Performance (p = 0.036). Novelty indicators reveal that business governance and ethics strongly represent Business Reputation, with loadings of 0.931 and 0.944. Conclusions: Business Reputation and Organizational Justice are key drivers of Talent Management Strategies and Employee Retention, whereas Leadership plays an insignificant role. Limitations: The study is limited to Indonesian MSMEs and cross-sectional data. Contribution: It contributes by emphasizing ethical governance and fairness as essential elements in improving MSME talent retention and performance.